The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.neuroimage.2016.08.014
|View full text |Cite
|
Sign up to set email alerts
|

The fornix provides multiple biomarkers to characterize circuit disruption in a mouse model of Alzheimer's disease

Abstract: Multivariate biomarkers are needed for detecting Alzheimer’s disease (AD), understanding its etiology, and quantifying the effect of therapies. Mouse models provide opportunities to study characteristics of AD in well-controlled environments that can help facilitate development of early interventions. The CVN-AD mouse model replicates multiple AD hallmark pathologies, and we identified multivariate biomarkers characterizing a brain circuit disruption predictive of cognitive decline. In vivo and ex vivo magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 104 publications
0
36
0
Order By: Relevance
“…This allows to model the human innate immune response, in particular with respect to the redox microenvironment, and NO production (Hoos et al, 2014). Mouse models on this genetic background expressing APP mutations present multiple AD like phenotypes (Wilcock et al, 2008;Colton et al, 2014;Kan et al, 2015;Badea et al, 2016). Here we assessed the differential effects of the interaction of the humanized NOS background with APOE3 and APOE4 alleles.…”
Section: Discussionmentioning
confidence: 99%
“…This allows to model the human innate immune response, in particular with respect to the redox microenvironment, and NO production (Hoos et al, 2014). Mouse models on this genetic background expressing APP mutations present multiple AD like phenotypes (Wilcock et al, 2008;Colton et al, 2014;Kan et al, 2015;Badea et al, 2016). Here we assessed the differential effects of the interaction of the humanized NOS background with APOE3 and APOE4 alleles.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicates the APPSwDI/Nos2−/− ( CVN-AD) mouse model replicates multiple AD pathologies [ 31 ] , Badea et al (2016) identified multivariate biomarkers that appear to predict cognitive decline. One of these biomarkers is the fornix.…”
Section: G Enetic and B Iological mentioning
confidence: 99%
“…Further reductions in acquisition times come from compressed sensing [28], which several groups have implemented for mouse MRI [29][30][31]. Such advances can help translate diffusion protocols into population studies [32] incorporating multiple biomarkers from morphometry [33], microstructural properties based on diffusion [13] or magnetic susceptibility [34], or network properties [35]. Such integrative studies may better predict changes in behaviors, modeling those observed in humans with neurodegenerative conditions [34].…”
Section: Discussionmentioning
confidence: 99%
“…We need to compare 2-mm linear dimension voxel sizes in humans (corresponding to 8-mm 3 voxel volumes), vs. 0.2-0.043-mm linear dimension voxel sizes (corresponding to ∼8 × 10 −2 -8 × 10 −5 -mm 3 voxel volumes) required to distinguish similar levels of anatomical detail in mouse brains [6][7][8][9][10][11]. This increased resolution enables the observation of brain architecture at the level of cellular layers, which, therefore, can help us gain insight into the mechanistic drivers behind the etiology and progression of disease, using animal models where axonal dimensions are relatively similar to humans [12,13].…”
Section: Introductionmentioning
confidence: 99%